2009
DOI: 10.4049/jimmunol.0803991
|View full text |Cite|
|
Sign up to set email alerts
|

Increase in ALK1/ALK5 Ratio as a Cause for Elevated MMP-13 Expression in Osteoarthritis in Humans and Mice

Abstract: During osteoarthritis (OA) chondrocytes show deviant behavior resembling terminal differentiation of growth-plate chondrocytes, characterized by elevated MMP-13 expression. The latter is also a hallmark for OA. TGF-beta is generally thought to be a protective factor for cartilage, but it has also displayed deleterious effects in some studies. Recently, it was shown that besides signaling via the ALK5 (activin-like kinase 5) receptor, TGF-beta can also signal via ALK1, thereby activating Smad1/5/8 instead of Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
278
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(297 citation statements)
references
References 36 publications
15
278
3
1
Order By: Relevance
“…Indeed, recent works have shown that leptin inhibits chondrogenesis [26]. Blaney Davidson et al showed an increased ALK-1/ALK-5 ratio as a cause of deviant chondrocyte behavior (elevated MMP-13 expression), which contributes to age-related cartilage destruction and osteoarthritis in humans [27,28]. Our results suggest that leptin may be one of the aspects of aberrant chondrocytes differentiation that results from changes in TGF-b signalling related to age or osteoarthritis.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, recent works have shown that leptin inhibits chondrogenesis [26]. Blaney Davidson et al showed an increased ALK-1/ALK-5 ratio as a cause of deviant chondrocyte behavior (elevated MMP-13 expression), which contributes to age-related cartilage destruction and osteoarthritis in humans [27,28]. Our results suggest that leptin may be one of the aspects of aberrant chondrocytes differentiation that results from changes in TGF-b signalling related to age or osteoarthritis.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to the possible role of the SASP and oxidative stress/damage, other changes occur: an accumulation of advanced glycation end-products that make the tissue more brittle; a reduction in the size of aggrecan with resultant decreased hydration that would reduce cartilage resiliency; an increase in collagen cleavage that would reduce tensile strength; increased matrix calcification that would alter mechanical properties and activate inflammatory pathways; and a reduced response to growth factors, including insulin-like growth factor 1 (IGF-1) and transforming growth factor-β (TGF-β) that would reduce repair [10]. The altered response to TGF-β appears to occur at the receptor level due to changes in the ratio of ALK1 to ALK5 promoting more catabolic relative to anabolic activity [1,14], and for IGF-1, an altered balance of MAP kinase and Akt signaling due to ROS may be playing a role [15]. Other findings on OA chondrocytes that also might be linked to aging include reduced levels of Sirt1, a potential positive regulator of cartilage matrix gene expression [4,6], and a decline in AMPK activity, which could also promote a pro-catabolic state [13].…”
Section: Physiology Of Aging and Oamentioning
confidence: 99%
“…Nanoparticles targeted to hypertrophic chondrocytes could also be used to improve the clinical translatability of resveratrol (a SIRT1 activator), rapamycin (a suppressor of mammalian target for rapamycin (mTOR), a negative regulator of autophagy) and Z-VAD-FMK (a pan-caspase inhibitor), in OA. [19][20][21] As an alternative to inhibiting transcription factors or activating bioenergy sensors in chondrocytes, blocking upstream signalling through receptors that have a part in chondrocyte hypertrophy, for example, activin-like kinase 1 (ALK1), 11,12 discoidin domain receptor-2 (DDR2), 22 syndecan-4 (SYND4), 23 and toll-like receptor 2 and 4 (TLR2/4), 24 by means of specific receptor antagonists can interfere with OA progression. Novel OA therapies aimed at interfering with the signalling through these receptors would benefit from using degradable nanoparticles targeted to damaged cartilage components.…”
mentioning
confidence: 99%
“…5 Many transcription factors, including runt-related transcription factor-2 (RUNX2), 7 HIF-2α, 8,9 CCAAT/enhancer-binding protein-β (C/EBPβ) 10 and small mothers against decapentaplegic 1/5/8 (Smad1/5/8), 11,12 to name a few, have been identified as targets and their inhibition has been regarded as an ideal therapeutic strategy for OA. However, the activation of many of these transcription factors is not constant during OA development-for example, HIF-2α is overexpressed in early and progressive stages of OA but is downregulated in the late stages of OA 9 -which makes the time window for the therapeutic use of gene inhibitors potentially narrow.…”
mentioning
confidence: 99%
See 1 more Smart Citation